2020
DOI: 10.1002/cnr2.1318
|View full text |Cite
|
Sign up to set email alerts
|

Vascular co‐option and vasculogenic mimicry mediate resistance to antiangiogenic strategies

Abstract: Background:The concept that all the tumors need the formation of new vessels to grow inspired the hypothesis that inhibition of angiogenesis would have led to "cure" cancer. The expectancy that this type of therapy would have avoided the insurgence of resistance was based on the concept that targeting normal vessels, instead of the cancer cells which easily develop new mutations, would have allowed evasion of drug caused selection is, however, more complex as it was made apparent by the discovery of nonangioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…However, no statistically significant difference among the three drugs is apparent with regard to progression free survival [ 35 ]. An animal study has revealed blockage of angiogenesis under cabozantinib, whilst tumors become more infiltrative and escape treatment [ 36 ]. These findings point to a mechanism similar to the one shown for sorafenib in counteracting sunitinib resistance by interfering with pathways connected to angiogenesis, but not to cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…However, no statistically significant difference among the three drugs is apparent with regard to progression free survival [ 35 ]. An animal study has revealed blockage of angiogenesis under cabozantinib, whilst tumors become more infiltrative and escape treatment [ 36 ]. These findings point to a mechanism similar to the one shown for sorafenib in counteracting sunitinib resistance by interfering with pathways connected to angiogenesis, but not to cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, patients with VM formation were more likely to suffer from tumor relapse, suggesting that VM may promote tumor progression. It has been reported that chemotherapeutic stress can promote VM, which in turn mediates resistance to anti-angiogenic therapy [35,36]. VM formation has been blamed for the unexpected adverse outcome after anti-angiogenic treatment in the triple-negative breast cancer, uveal melanoma and ovarian cancer [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Alternative mechanisms of tumor vasculature, including intussusceptive microvascular growth (IMG), vasculogenic mimicry, and vascular co-option, are involved in resistance to anti-angiogenic therapies [ 32 , 33 ], but again, anti-angiogenic treatments have been so far provided without evaluating whether the tumors are angiogenic or not or in which proportions a tumor is angiogenic or not angiogenic [ 34 ]. IMG, in which the capillary network increases its complexity by insertion of a multitude of transcapillary pillars, has been observed in different human tumors, including melanoma, colon and breast carcinoma, lymphoma, and glioblastoma [ 32 ].…”
Section: Alternative Mechanisms Of Tumor Vasculaturementioning
confidence: 99%